Intended and Unintended Effects of E-cigarette Taxes on Youth Tobacco Use - Rahi Abouk; Charles Courtemanche; Dhaval M. Dave; Bo Feng; Abigail S. Friedman; J. Catherine Maclean; Michael Pesko; Joseph J. Sabia; Samuel Safford (Institute of Labor Economics (IZA), 2022)
Over the past decade, rising youth use of e-cigarettes and other electronic nicotine delivery systems (ENDS) has contributed to aggressive regulation by state and local governments. Between 2010 and mid-2019, ten states and two large counties adopted ENDS taxes. We use two large national surveys (Monitoring the Future and the Youth Risk Behavior Surveillance System) to estimate the impact of ENDS taxes on youth tobacco use. We find that ENDS taxes reduce youth ENDS consumption, with estimated ENDS tax elasticities of -0.06 to -0.21. However, we estimate sizable positive cigarette cross-tax effects, suggesting economic substitution between cigarettes and ENDS for youth. These substitution effects are particularly large for frequent cigarette smoking. We conclude that the unintended effects of ENDS taxation may considerably undercut or even outweigh any public health gains.
Keywords: H2; I1; I18; 330; electronic nicotine delivery systems (ENDS); e-cigarettes; vaping; cigarettes; smoking; taxes; youth